High-performance carbon/MnO2 micromotors and their applications for pollutant removal. (March 2019) - He, Xu; Büchel, Robert; Figi, Renato; Zhang, Yucheng; Bahk, Yeonkyoung; Ma, Jun; Wang, Jing
Abstract: The wide applications of particulate micromotors in practice, especially in the removal of environmental pollutants, have been limited by the low production yields and demand on high concentration of fuel such as H2 O2 . Carbon/MnO2 micromotors were made hydrothermally using different carbon allotropes including graphite, carbon nanotube (CNT), and graphene for treatment of methylene blue and toxic Ag ions. The obtained micromotors showed high speed of self-propulsion. The highest speed of MnO2 -based micromotors to date was observed for CNT/MnO2 (>2 mm/s, 5 wt% H2 O2, 0.5 wt% surfactant). Moreover, different from previous studies, even with low H2 O2 concentration (0.5 wt%) and without surfactant addition, the micromotors could also be well dispersed in water by the O2 stream released from their reaction with H2 O2 . The carbon/MnO2 micromotors removed both methylene blue (>80%) and Ag ions (100%) effectively within 15 min by catalytic decomposition and adsorption. Especially high adsorption capacity of Ag (600 mg/g) was measured on graphite/MnO2 and graphene/MnO2 micromotors. Highlights: C/MnO2 micromotors were synthesized by simple hydrothermal methods with low cost. The C/MnO2 micromotors could move with ultrafast speed and disperse in water without the addition of surfactant. High pollutant removal efficiency was achieved for both Methylene blue and Ag ions within 15 min.